2013
DOI: 10.2224/sbp.2013.41.3.463
|View full text |Cite
|
Sign up to set email alerts
|

Key Factors for Knowledge Management Implementation

Abstract: Although ethical climate, trust, satisfaction, and commitment are related to knowledge management (KM), there are at present few studies in which the way ethical climate affects KM through trust, satisfaction, and commitment has been emphasized. Our aim was to fill this research gap by examining different ethical climates in this context. We found that principleoriented climates of company rules and procedures (CRP) and laws and professional codes (LPC) affected KM positively and directly, the benevolence-orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Ethical leaders communicate ethical values to create an inclusive learning environment in the workplace (Walumbwa et al, 2017). A system of ethical values in an organisation can encourage members to store and apply collective knowledge due to their sense of moral obligation and shared interest (Luo and Lee, 2013). Tseng and Fan (2011) found that an ethical organisational climate can significantly influence employee engagement in knowledge management.…”
Section: Mediating Role Of Team Learningmentioning
confidence: 99%
“…Ethical leaders communicate ethical values to create an inclusive learning environment in the workplace (Walumbwa et al, 2017). A system of ethical values in an organisation can encourage members to store and apply collective knowledge due to their sense of moral obligation and shared interest (Luo and Lee, 2013). Tseng and Fan (2011) found that an ethical organisational climate can significantly influence employee engagement in knowledge management.…”
Section: Mediating Role Of Team Learningmentioning
confidence: 99%
“…However, organizations are still requested to offer the highest level of trust between individuals. The failure to achieve a sufficient level of mutual trust can make individuals doubt their colleagues' behaviors and intentions; as a result, they will likely refuse to provide or share their knowledge (Luo & Lee, ). This can lead to major conflicts in knowledge uploading into KMS (Luo & Lee, ).…”
Section: Discussionmentioning
confidence: 99%
“…To integrate CSR into a firm's daily operations, the concerns of stakeholders are important aspects to consider (Guadamillas-G omez et al, 2010). Although both CSR and KM are important antecedent of organizational performance (Kavitha and Anita, 2011;Misani, 2010;Ling, 2013), many studies examine only the individual influence of CSR (McDermott, 2009;Huang, 2010) or KM (Caddy et al, 2001;Li and Gao, 2003;Yang, 2007;Luo and Lee, 2013) on organizational performance.…”
Section: Research Backgroundmentioning
confidence: 99%